Examining the relationship between encouragement and health-related quality of life among Muslims. (3rd July 2017) - Hodge, David R.; Zidan, Tarek; Husain, Altaf
ABSTRACT: This study examines the relationship between encouragement and health-related quality of life (HRQOL) among a sample of American Muslims, in tandem with the potential mediating effects of depression and spirituality. To conduct this cross-sectional study, a model was developed and tested using structural equation modeling (SEM) with a community sample of Muslims (N = 284). The results indicate that encouragement has a direct, positive effect on HRQOL. Neither depression nor spirituality mediated the relationship between encouragement and HRQOL. Rather, both variables exhibited a direct, independent effect on HRQOL. In addition, spirituality exhibited an indirect effect on HRQOL through attenuating depression. The findings underscore the importance of encouragement as a pathway to enhance HRQOL among Muslims in post-9/11 America. The results also suggest that spirituality can play a significant role in fostering HRQOL among Muslims, both directly and indirectly by reducing the effects of depression on HRQOL.